Stress effect on the orientation and the arrangement of H‐platelets. Issue 1 (29th November 2012) - Vallet, Maxime; Reboh, Shay; Beaufort, Marie‐France; Grilhé, Jean; Barbot, Jean François
Abstract The effect of stress on the formation energy of H‐platelets was studied through a 3D model based on elastic interaction by modelling the platelets as dislocation loops. A difference of self‐formation energy between 111 and 100 platelets was estimated by comparing the calculations with experimental results. When a local source of stress is added to the implantation‐induced stress, different types of platelets could form according to the symmetry of the local stress field. Besides, their arrangement at a nanometre scale makes specific architecture depending on the crystallographic orientation of the surface, 〈001〉‐, 〈011〉‐, or 〈111〉‐orientation. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)